2008
DOI: 10.1016/j.juro.2008.04.027
|View full text |Cite
|
Sign up to set email alerts
|

Whole Gland Primary Prostate Cryoablation: Initial Results From the Cryo On-Line Data Registry

Abstract: Whole gland cryoablation, practiced in a spectrum of academic and community users, maintains efficacy and morbidity similar to that of single center reports.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
72
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(81 citation statements)
references
References 18 publications
3
72
1
1
Order By: Relevance
“…The percutaneous needle ablation simplifies surgery compared to other therapies such as open, laparoscopic or robotic prostatectomy. Outcomes from the Cryo On-Line Data registry reported that among the 1.198 consecutive patients who underwent primary cryoablation, 3.6% of patients developed urinary retention and 0.4% rates of recto-urethral fistulas (23). In our study, no recto-urethral fistula was observed.…”
Section: Resultssupporting
confidence: 43%
See 1 more Smart Citation
“…The percutaneous needle ablation simplifies surgery compared to other therapies such as open, laparoscopic or robotic prostatectomy. Outcomes from the Cryo On-Line Data registry reported that among the 1.198 consecutive patients who underwent primary cryoablation, 3.6% of patients developed urinary retention and 0.4% rates of recto-urethral fistulas (23). In our study, no recto-urethral fistula was observed.…”
Section: Resultssupporting
confidence: 43%
“…They concluded that prostate cryoablation is a minimally invasive treatment with promising results, resulting in low complication rates for high risk patients with prostate cancer (24). Jones et al using the COLD registry database reported a 5-year BDFS in 1.198 patients using the Phoenix criteria of 91%, 78%, and 62% for low, moderate, and high risk respectively (23). Cohen et al demonstrated a 10 year BDFS of 80.6%, 74.2%, and 45.5% for low, moderate, and high risk patients using the Phoenix criteria (25).…”
Section: Resultsmentioning
confidence: 99%
“…These biochemical results compare quite favourably to the results of radiation therapy as a monotherapy. 21 A recent randomized trial comparing cryotherapy with radiation therapy reported similar biochemical outcomes and a significantly lower rate of positive post-treatment biopsies in the cryotherapy-treated patients. 22 Cryosurgery leaves tumour proteins and tumour-associated antigens intact.…”
Section: Discussionmentioning
confidence: 91%
“…The inclusion criteria were as follows: patients with prehormone therapy high-risk features of PCa, which were defined as either a prostate-specific antigen (PSA) level o10 ng ml 21 , a pathology report indicating a Gleason sum score o8, or both; no previous hormonal, immunosuppressive, or radiation therapy before this treatment; and no evidence of metastatic disease by bone scan, computer-assisted tomography, or magnetic resonance imaging. The patient characteristics are summarized in Table 1.…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…Currently, these two treatment methods are used as primary treatments for men who are poor surgical candidates and want to avoid radiation therapy treatments [38]. However, local recurrence of PCa after CS or HIFU treatment has emerged as a serious problem for which a feasible management solution is still unknown [39,40]. There are conflicting recommendations for both CS and HIFU as alternative primary treatment options due to lack of controlled studies, limited follow-ups and limited information on cancer-specific survival.…”
mentioning
confidence: 99%